PENGARUH CORPORATE GOVERNANCE DAN RETURN ON ASSET TERHADAP TAX A VOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2012—2014 - Rubiatto Biettant (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2015)
The purpose of this study was to determine the effect of corporate governance and return on assets against tax avoidance in manufacturing companies on the BEI in 2012-20;4. The research data was obtained from the company's annual finance report on the Indonesian stock exchange website. The samples are 34 companies mwmfacturing sector listed on the Stock Exchange in 2012-2014. Sampling technique used is purposive sampling. This study uses linear regression analysis. The results showed that corporate governance has not significant effect on tax avoidance. The results show that corporate governance and return on assets have a significant effect on tax avoidance